Features of lipid metabolism in chronic heart failure of different genesis with concomitant overweight and obesity - Р. P. Bidzilya (Zaporožskij Medicinskij Žurnal)
Recently clinical studies demonstrated reciprocal association between traditional cardiovascular risk factors, in particular, hyperlipidemia and obesity, with worse clinical outcomes in CHF. Unlike ischemic heart disease (IHD), where high levels of atherogenic and low of antiatherogenic lipids fraction traditionally associated with worsening of prognosis and course of disease, in conditions of the CHF proven negative impact of the reduction of lipid levels and body mass index. Demonstrated the phenomena called "cholesterol paradox" and "obesity paradox".